2016
DOI: 10.4103/0972-124x.168486
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peri-implant soft tissue and bone levels around early loaded implant in restoring single missing tooth: A clinico-radiographic study

Abstract: Background:One-stage nonsubmerged protocol which can achieve success rates comparable to implants placed in a two-staged submerged procedure also the preconditions for periimplant bone regeneration has lead to more refined concepts of implant loading.Materials and Methods:Twenty sites with single missing tooth were included in this study. Clinical parameters included sulcus bleeding index (sBI), probing pocket depth (PD), and papilla index (PI) and radiographic parameters included crestal bone level were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…This is similar to the 2‐month results in our previous trial with Brånemark implants. Others have reported greater resorption at similar time points with other implant designs (Bhardwaj, Bhushan, Sudha Baiju, Bali, & Joshi, ).…”
Section: Discussionsupporting
confidence: 55%
“…This is similar to the 2‐month results in our previous trial with Brånemark implants. Others have reported greater resorption at similar time points with other implant designs (Bhardwaj, Bhushan, Sudha Baiju, Bali, & Joshi, ).…”
Section: Discussionsupporting
confidence: 55%
“…This depicts that in both immediate loaded dental implant and non-loaded dental implants, there is a slight difference in BOP index. Bhardwaj et al 9 assessed sulcus bleeding index, papilla index and probing pocket depth in immediate loaded dental implants in single missing tooth found that at baseline the mean crestal bone loss was 0.25 mm which increased 0.88 mm after 9 months. Similarly, PPD found to be the same at 3 weeks and after 9 months.…”
Section: Discussionmentioning
confidence: 99%
“…This is in harmony with Bhardwaj et al in 2016 who revealed insignificant changes in probing depths at 3, 6, 9 and 12 months of implant loading. (31) Such finding was based on the fact that formation and maturation of the barrier function of junctional epithelium around implant abutments requires 6-8 weeks of healing and stabilization which acts as a barrier between the contaminated oral cavity and marginal bone. (32) Regarding the modified sulcus bleeding index, no statistical significant differences were found between all groups at (T0), (T1), (T2) (P=0.822, 0.211, 0.149 respectively).…”
Section: Discussionmentioning
confidence: 99%